Perencanaan Pemenuhan Kebutuhan Parkir Pasar Mangkang Terhadap Kinerja Ruas Jalan Jenderal Urip Sumoharjo, Kota Semarang - Fandi, Muhammad (Jurnal Civil Engineering Study, 2023)
The driver's vehicle is in a state of rest when it is parked. However, the need for parking space is a serious problem for all groups. Mangkang Market is one of the markets that requires sufficient parking space for market activities. Because of this, research on parking fulfillment planning for the Mangkang market was carried out using a quantitative descriptive method to find out the parking space requirements for the Mangkang market. The results of this study indicate that the highest degree of saturation reaches 1.0538, which means that traffic flow in the area is hampered. Due to the insufficient parking area, which is only 493.5 m2, the parking requirement that must be met is 566 m2.